2022
DOI: 10.1055/a-1849-5594
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Nasal Valve Treatment

Abstract: Nasal valve insufficiency can be addressed using endonasal and open structure surgical techniques. However, some patients may prefer or be better suited for minimally invasive techniques that allow for more expedient treatment in the clinical setting. Techniques include internal dilators, external dilators, suture suspension, lateral wall implants, and radiofrequency remodeling. Understanding the indications for each technique as well as the available evidence can help facial plastic surgeons assess the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…The stylus is marketed for use on the inferior turbinates, septal swell bodies, and the upper lateral cartilages to augment the internal nasal valve. 45,46 In a prospective analysis, Ephrat et al 47 showed that patients treated with VivAer maintained symptom improvement for 2 years following the procedure based off results from the Nasal Obstruction Symptom Evaluation (NOSE) survey. This implies that some of the morphologic changes to the cartilage from this device may last at least 2 years or potentially longer.…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…The stylus is marketed for use on the inferior turbinates, septal swell bodies, and the upper lateral cartilages to augment the internal nasal valve. 45,46 In a prospective analysis, Ephrat et al 47 showed that patients treated with VivAer maintained symptom improvement for 2 years following the procedure based off results from the Nasal Obstruction Symptom Evaluation (NOSE) survey. This implies that some of the morphologic changes to the cartilage from this device may last at least 2 years or potentially longer.…”
Section: Radiofrequency Ablationmentioning
confidence: 99%